2014
DOI: 10.3322/caac.21258
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, pathophysiology, and management of noncentral nervous system cancer‐related cognitive impairment in adults

Abstract: Over the past few decades, a body of research has emerged confirming what many adult patients with noncentral nervous system cancer have long reported—that cancer and its treatment are frequently associated with cancer-related cognitive impairment (CRCI). The severity of CRCI varies, and symptoms can emerge early or late in the disease course. Nonetheless, CRCI is typically mild to moderate in nature and primarily involves the domains of memory, attention, executive functioning, and processing speed. Animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
422
1
40

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(493 citation statements)
references
References 235 publications
(518 reference statements)
11
422
1
40
Order By: Relevance
“…However, besides well known immediate side effects, such as nausea, chemotherapy has also been associated with long-term negative consequences, such as cardiovascular disease [2] and the potential neurotoxicity of chemotherapy [3,4] through possible disturbance of various mechanisms including apoptosis and suppressed neurogenesis [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, besides well known immediate side effects, such as nausea, chemotherapy has also been associated with long-term negative consequences, such as cardiovascular disease [2] and the potential neurotoxicity of chemotherapy [3,4] through possible disturbance of various mechanisms including apoptosis and suppressed neurogenesis [5].…”
mentioning
confidence: 99%
“…We will also examine a 'dose-response relationship' by distinguishing patients who were treated with standard dose chemotherapy from those for whom standard dose chemotherapy was unsuccessful and who were therefore treated with supplementary high dose chemotherapy. In addition, because not all patients may be equally affected [4], we will also examine whether a subgroup of patients have deviant cognitive function. If so, we will explore possible neuro-epidemiological differences such as protective 'cognitive reserve' [3,4,16] and younger age [10] between patients with deviant cognitive function and patients with normal cognitive function.…”
mentioning
confidence: 99%
“…These adverse effects were noted in the patient's medical record and are not a result of the aging process. The changes were so pronounced that (based on literature review) cancer-related cognitive dysfunction may be suspected (Hermelink et al, 2017;Isenberg-Grzeda & Ellis, 2017;Johns et al, 2016;Wefel et al, 2015).…”
Section: Resultsmentioning
confidence: 98%
“…The level of dysfunction, however, is a very individual feature (Hermelink et al, 2017;Wefel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies of men with various cancers have identified that 16-48% had lower-than-normal cognitive performance prior to cancer treatment (Janelsins et al 2014, Wefel et al 2015. As cognitive function is rarely measured prior to ADT administration, many studies are observational, and few studies have provided a measure of estimated cognitive reserve.…”
Section: The Effects Of Androgen Deprivation On Cognitive Functionmentioning
confidence: 99%